2. (06.01) If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to y from the first equation is substituted into the second equation. 15x − y = −6 5x − 3y = −13 (1 point) 5(−15x − 6) − 3y = −13 5(15x + 6) − 3y = −13 5x − 3(15x + 6) = −13 5x − 3(−15x − 6) = −13

QUESTION POSTED AT 29/05/2020 - 04:12 PM

Answered by admin AT 29/05/2020 - 04:12 PM

15x - y = -6......15x + 6 = y...now we sub this into the other equation and get :

5x - 3y = -13.....
5x - 3(15x + 6) = -13 <===
Post your answer

Related questions

The expression 3 × 7 – 4 × 8 + 2 is equivalent

QUESTION POSTED AT 02/06/2020 - 01:42 AM

Find the six arithmetic means between 1 and 29.

QUESTION POSTED AT 02/06/2020 - 01:36 AM

How do you factor the second equation?

QUESTION POSTED AT 02/06/2020 - 01:31 AM